Molluscks Melampidae (Pulmonata: Gastropoda) in the estuarine areas of the Red river - Khac, Hoang Ngoc; Nhuong, Do Van; Hai, Ho Thanh (Academia Journal of Biology, 2012)
Based on analysis of melampid shells (Melampidae: Pulmonata: Gastropoda) collected from mangrove areas of the Red River during 2005 - 2009, 15 species of melampid belonging to 7 genera (Melampus, Laemodonta, Ellobium, Cassidula, Pythia, Auriculastra, Cylindrotis) have been recorded. Of which, 1 species have not yet identified. In species composition, genus Cassidula is the most abundant of species (4 species), next are Melampus and Laemodonta (3 species), Ellobium (2 species) and finally Auriculastra, Cylindrotis, Pythia only 1 species. Research results have added 9 species for the snail fauna of the coastal zone of Vietnam in general and of the studied area in particular, there are: Melampus fasciatus, Melampus parvulus, Melampus graminea, Laemodonta octanfracta, Laemodonta exaratoides, Laemodonta punctatostriata, Cassidula mustelina, Cassidula sowerbyana, Cassidula sp.1, Auriculastra subula and Cylindrotis quadrasi. However, the shell of large size - Ellobium aurismidae (Linnaeus, 1758) was not found in this area. The key for identification of melampid genus and species occurred in estuarine area of the Red river is compiled by the author. The descriptions of all species and their figures are also given in this paper.